Analysis of genetic diversity among current spring wheat varieties and breeding for improved yield stability of wheat (Triticum aestivum L.) - Hai, Lin; Justus Liebig University Giessen (My University, 2006)
Genetic diversity in spring bread wheat (T. aestivum L.) was studied in a total of 69 accessions. For this purpose, 52 microsatellite (SSR) markers were used and a total of 406 alleles were detected, of which 182 (44.8%) occurred at a frequency of < 5% (rare alleles). The number of alleles per locus ranged from 2 to 14 with an average of 7.81. The largest number of alleles per locus occurred in the B genome (8.65) as compared to the A (8.43) and D (5.93) genomes, respectively. The polymorphism index content (PIC) value varied from 0.24 to 0.89 with an average of 0.68. The highest PIC for all accessions was found in the B genome (0.71) as compared to the A (0.68) and D genomes (0.63). Genetic distance-based method (standard UPGMA clustering) and a model-based method (structure analysis) were used for cluster analysis. The two methods led to analogical results. Analysis of molecular variance (AMOVA) showed that 80.6% of the total variation could be explained by the variance within the geographical groups. In comparison to the diversity detected for all accessions (He = 0.68), genetic diversity among European spring bread wheats was He = 0.65. A comparatively higher diversity was observed between wheat varieties from Southern European countries (Austria/Switzerland, Portugal/Spain) corresponding to those from other regions.

Eine erfolgversprechende Verbesserung von Kulturpflanzen setzt das Vorhandensein und die Nutzbarkeit genetischer Diversität voraus. Eine Kenntnis über den Grad und die Verteilung genetischer Diversität stellt daher eine wichtige Grundlage für die Entwicklung geeigneter Strategien zur optimalen Nutzung der verfügbaren genetischen Ressourcen dar.
Keywords: genetische Diversität; genetic diversity; microsatellites; qualitative structure analysis; ddc:630